Cognard Type V Intracranial Dural Arteriovenous Shunt: Case Reports and Literature Review With Special Consideration of the Pattern of Spinal Venous Drainage. Issue 1 (8th July 2013) - Haryu, Shinya; Endo, Toshiki; Sato, Kenichi; Inoue, Takashi; Takahashi, Akira; Tominaga, Teiji
Abstract: BACKGROUND AND IMPORTANCE: Prompt diagnosis of intracranial dural arteriovenous shunt (DAVS) with spinal venous drainage, classified as Cognard type V, is difficult. We investigated the angiographic and magnetic resonance imaging (MRI) characteristics of Cognard type V DAVS to determine the reason for the difficulty in early diagnosis. CLINICAL PRESENTATION: We systematically reviewed 54 published and 3 new cases of Cognard type V DAVS. The pattern of venous drainage was classified on the basis of relative dominance of the anterior and posterior spinal veins with the use of angiograms. T2-weighted sagittal MRIs were used to detect signal flow voids of enlarged spinal veins. Types of venous drainage were determined in 49 of the 57 cases. Twenty-eight and 8 cases showed a dominance of anterior and posterior spinal venous drainage, respectively. In 13 cases, venous drainage was equally distributed through the anterior and posterior spinal veins. Of 41 cases with an abnormally dilated anterior spinal vein, MRIs were available for 25 cases. Signal flow voids of enlarged anterior spinal veins were detected in 9 cases (36.0%), whereas dilatation of the posterior spinal veins was apparent in 9 of 16 cases (56.3%). Overall, MRI detected enlargement of either anterior or posterior spinal veins in 15 of 41 cases (36.6%). CONCLUSION: In Cognard type V DAVS, anterior venous drainage is dominant. Because the anterior spinal veins are located subpially, flow voids are less prominent on sagittal T2-weighted MRI. This may lead to difficulties in diagnosing. Evaluation with MR angiography may compensate for these limitations.